Attentional Sets Influence Perceptual Load Effects, but not Dilution Effects. Issue 4 (April 2014) - Benoni, Hanna; Zivony, Alon; Tsal, Yehoshua
Perceptual load theory [Lavie, N. (1995). Perceptual load as a necessary condition for selective attention. Journal of Experimental Psychology: Human Perception and Performance, 21, 451–468.; Lavie, N., & Tsal, Y. (1994) Perceptual load as a major determinant of the locus of selection in visual attention. Perception & Psychophysics, 56, 183–197.] proposes that interference from distractors can only be avoided in situations of high perceptual load. This theory has been supported by blocked design manipulations separating low load (when the target appears alone) and high load (when the target is embedded among neutral letters). Tsal and Benoni [(2010a). Diluting the burden of load: Perceptual load effects are simply dilution effects. Journal of Experimental Psychology: Human Perception and Performance, 36, 1645–1656.; Benoni, H., & Tsal, Y. (2010). Where have we gone wrong? Perceptual load does not affect selective attention. Vision Research, 50, 1292–1298.] have recently shown that these manipulations confound perceptual load with "dilution" (the mere presence of additional heterogeneous items in high-load situations). Theeuwes, Kramer, and Belopolsky [(2004). Attentional set interacts with perceptual load in visual search. Psychonomic Bulletin & Review, 11, 697–702.] independently questioned load theory by suggesting that attentional sets might also affect distractor interference. When high load and low load were intermixed, and participants could not prepare for the presentation that followed, both the low-load and high-load trials showed distractor interference. This result may also challenge the dilution account, which proposes a stimulus-driven mechanism. In the current study, we presented subjects with both fixed and mixed blocks, including a mix of dilution trials with low-load trials and with high-load trials. We thus separated the effect of dilution from load and tested the influence of attentional sets on each component. The results revealed that whereas perceptual load effects are influenced by attentional sets, the dilution component is not. This strengthens the notion that dilution is a stimulus-driven mechanism, which enables effective selectivity.